Strategi Pengembangan Kompetensi Sumber Daya Manusia Pasca Unloading dari Kapal Ternak Camara Nusantara Indonesia - G. M. Toharmat; A. M. Fuah; L. Cyrilla; Y. Triyonggo (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2020)
The purpose of this study was to create strategy for developing Human Resource competency post unloading from Camara Nusantara Cattle Ship. Analytic Hierarchy Process (AHP) method were used for search the best alternative strategy for developing Human Resource competency post unloading from Camara Nusantara Cattle Ship. The expert selection was carried out to obtain priority weights or rankings in the AHP structure to determine post-unloading HR competency development strategies. Based on the results of the analysis that has been done that the most influential factor is facilities and infrastructure with a weight of 0.377. The actor who has the most role in determining the strategy to increase the competence of human resources after unloading from cattle ship is an expedition company with a weight of 0.269, with the primary objective being to maintain the quality of livestock (0.464). The most appropriate alternative strategy in the hierarchy with a weight of 0.324 is conducting competency-based training and development.